Kinematic analysis between three groups according to proficiency in fencer's Fente movement - Jo, H. D.; Park, H. Y. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study is to analyse and comparison the differences of kinematic variables for Fente skill in Fencing. Method: For this, 15 people were selected as 5 beginners with less than 2 years of experience, 5 intermediate-class people with more than 2 years and less than 4 years, and 5 experts-class people with more than 4 years. Through the comparison of Marche Fente motion according to proficiency, for the necessary time, travel distance, the kinematical factor of joint angle, oneway ANOVA was performed in order to identify differences according to variables by phase. Results: The time required for each phase was shown to be shorter for all phases experts than for beginners and intermediates. At the horizontal displacement of the foot, the right foot left out the last phase and the experts appeared long. The left foot showed short beginners in all phases. The angle of forward lean showed that the angle of forward lean was tilted forward by the experts of all phases. There was a difference between the left and right joint angles of the lower limb, both of the ankle, knee and hip joints. Conclusion: In overall, Beginners should quickly widen the distance of their feet when they make a Fente movement. The beginner shall tilt the upper body forward in order to increase the angle of forward lean. The beginner shall, in the last phase, have a smaller angle on the hip joint.